2007
DOI: 10.1111/j.1600-051x.2007.01102.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of peri‐implantitis using a bone substitute with or without a resorbable membrane: a prospective cohort study

Abstract: It is possible to treat peri-implant defects with a bone substitute, with or without a resorbable membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 37 publications
(50 reference statements)
5
158
1
6
Order By: Relevance
“…Renvert et al 12 PPD, bleeding, plaque Hyperplasia, full-mouth plaque score, local plaque score, PPD at the worst site of implant, mean PPD, BOP, and bleeding (after PPD) Má ximo et al 13 PPD, bleeding, suppuration Plaque index (PI) ( 14 PPD, bleeding, plaque Bleeding on sampling (BOS), PPD in millimetres, full-mouth bleeding score (FMBS) (after PPD), bleeding on probing (BOP) (after PPD), full-mouth plaque score (FMPS), local plaque score (LPS) Schwarz et al 15 Plaque 18 Plaque, bleeding, recession, CAL Plaque index (PI), BOP, probing depth (PD), gingival recession (GR), clinical attachment level (CAL) Karring et al 19 Plaque, bleeding, PPD Plaque (PL), BOP, PPD Schwarz et al 20 Plaque, bleeding, recession, CAL Plaque index (PI) (Lö e 27 ), bleeding on probing (BOP), probing depth (PD), gingival recession (GR), clinical attachment level (CAL) Romeo et al 21 Suppuration, plaque, bleeding, PPD, recession, CAL 22 PPD, CAL, bleeding Pocket probing depth, probing attachment level, bleeding on probing Tang et al 23 PPD, BOP, plaque, Plaque index, probing pocket depth, bleeding upon probing 33 Immunological, radiographic ELISA (TNF-a, IL-4, IL-10, RANKL), OPG, periapical intraoral radiographs for each implant at baseline (paralleling technique and radiographically positioned) (peri-implant bone loss using abutments and the threads of the implants as reference points) Renvert et al 14 Culturing, DNA Culturing (TVC): Staphylococcus aureus, enteric rods, and enterococci; DNA-DNA hybridisation techniques: P. gingivalis, P. intermedia, P. nigrescens, T. forsythia, A. actinomycetemcomitans, Fusobacterium nucleatum, T. denticola, Parvimonas micra (previously Peptostreptococcus micros or Micromonas micros), Campylobacter rectus, Eikenella corrodens, Selenomonas noxia, and Streptococcus intermedius Schwarz et al 15 Radiographic Periapical radiographs with the long cone paralleling technique Roos-Janså ker et al 16 Radiographic Radiographs (parallel long cone standardised using individually made biteblocks on an Eggen holder (Renvert et al 36 ). Romeo et al 34 Radiographic Marginal bone loss (MBL) measurement system setting and MBL assessment: distance between implant neck and the most apical point of each fixture (red vertical line); implant neck height (yellow vertical line); implant neck diameter (blue horizontal line); peri-implant bone resorption mesial and distal to each implant (white vertical lines).…”
Section: Studies General Endpoints Specific Endpointsmentioning
confidence: 99%
“…Renvert et al 12 PPD, bleeding, plaque Hyperplasia, full-mouth plaque score, local plaque score, PPD at the worst site of implant, mean PPD, BOP, and bleeding (after PPD) Má ximo et al 13 PPD, bleeding, suppuration Plaque index (PI) ( 14 PPD, bleeding, plaque Bleeding on sampling (BOS), PPD in millimetres, full-mouth bleeding score (FMBS) (after PPD), bleeding on probing (BOP) (after PPD), full-mouth plaque score (FMPS), local plaque score (LPS) Schwarz et al 15 Plaque 18 Plaque, bleeding, recession, CAL Plaque index (PI), BOP, probing depth (PD), gingival recession (GR), clinical attachment level (CAL) Karring et al 19 Plaque, bleeding, PPD Plaque (PL), BOP, PPD Schwarz et al 20 Plaque, bleeding, recession, CAL Plaque index (PI) (Lö e 27 ), bleeding on probing (BOP), probing depth (PD), gingival recession (GR), clinical attachment level (CAL) Romeo et al 21 Suppuration, plaque, bleeding, PPD, recession, CAL 22 PPD, CAL, bleeding Pocket probing depth, probing attachment level, bleeding on probing Tang et al 23 PPD, BOP, plaque, Plaque index, probing pocket depth, bleeding upon probing 33 Immunological, radiographic ELISA (TNF-a, IL-4, IL-10, RANKL), OPG, periapical intraoral radiographs for each implant at baseline (paralleling technique and radiographically positioned) (peri-implant bone loss using abutments and the threads of the implants as reference points) Renvert et al 14 Culturing, DNA Culturing (TVC): Staphylococcus aureus, enteric rods, and enterococci; DNA-DNA hybridisation techniques: P. gingivalis, P. intermedia, P. nigrescens, T. forsythia, A. actinomycetemcomitans, Fusobacterium nucleatum, T. denticola, Parvimonas micra (previously Peptostreptococcus micros or Micromonas micros), Campylobacter rectus, Eikenella corrodens, Selenomonas noxia, and Streptococcus intermedius Schwarz et al 15 Radiographic Periapical radiographs with the long cone paralleling technique Roos-Janså ker et al 16 Radiographic Radiographs (parallel long cone standardised using individually made biteblocks on an Eggen holder (Renvert et al 36 ). Romeo et al 34 Radiographic Marginal bone loss (MBL) measurement system setting and MBL assessment: distance between implant neck and the most apical point of each fixture (red vertical line); implant neck height (yellow vertical line); implant neck diameter (blue horizontal line); peri-implant bone resorption mesial and distal to each implant (white vertical lines).…”
Section: Studies General Endpoints Specific Endpointsmentioning
confidence: 99%
“…Concerning the application of the disinfection technique to the treatment of oral infectious diseases, the metals would be exposed to hydroxyl radicals only for much shorter time than the case of denture cleaning. For instance, H 2O2 is clinically used for the treatment of peri-implantitis to clean the implant surface made of Ti 29,30) . Therefore, the corrosive effect of the disinfection solution containing hydroxyl radicals would be negligible in clinical treatments where the treatment is expected to be completed within a short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…14,20,84 Clinical studies have shown improvement in defect fill and probing depth when patients were treated with bone graft regardless of the use of resorbable membranes. 85 These materials have different properties and therefore their indications may vary. The use of the three classes of materials in diverse combinations depends upon the size and topography of the bony defect.…”
Section: Surgical Debridement and Bone Graftingmentioning
confidence: 99%